# Toán Lớp 8: a) 2(x-1)^2+(x+3)^2=3(x-2)(x+1) b) (4x^3+3x+1)(4x^3-3x+1)-(4x^3+1)^2=36 Giúp mk vs

By Thanh Hùng

Toán Lớp 8: a) 2(x-1)^2+(x+3)^2=3(x-2)(x+1)
b) (4x^3+3x+1)(4x^3-3x+1)-(4x^3+1)^2=36
Giúp mk vs

### 0 bình luận về “Toán Lớp 8: a) 2(x-1)^2+(x+3)^2=3(x-2)(x+1) b) (4x^3+3x+1)(4x^3-3x+1)-(4x^3+1)^2=36 Giúp mk vs”

1. $\begin{array}{l} a)2{\left( {x – 1} \right)^2} + {\left( {x + 3} \right)^2} = 3\left( {x – 2} \right)\left( {x + 1} \right)\\ \Leftrightarrow 2{x^2} – 4x + 2 + {x^2} + 6x + 9 = 3\left( {{x^2} – x – 2} \right)\\ \Leftrightarrow 3{x^2} + 2x + 11 = 3{x^2} – 3x – 6\\ \Leftrightarrow 5x = – 5 \Leftrightarrow x = – 1\\ b)(4{x^3} + 3x + 1)(4{x^3} – 3x + 1) – {(4{x^3} + 1)^2} = 36\\ \Leftrightarrow {\left( {4{x^3} + 1} \right)^2} – {\left( {3x} \right)^2} – {\left( {4{x^3} + 1} \right)^2} = 36\\ \Leftrightarrow – 9{x^2} = 36\\ \Leftrightarrow {x^2} = – 4\\ \Rightarrow x \in \emptyset \end{array}$

Trả lời
2. Giải đáp:

Lời giải và giải thích chi tiết:
a)
2(x-1)^2 + (x+3)^2 = 3(x-2)(x+1)
-> 3x^2 + 2x + 11 = 3x^2 – 3x – 6
-> 3x^2 + 2x = 3x^2 – 3x – 17
-> 2x = -3x – 11
-> 5x = -17
-> x = -17/5
Vậy x \in {-17/5}
b)
(4x^3+3x+1)(4x^3-3x+1)-(4x^3+1)^2 = 36
-> 16x^6 + 8x^3 – 9x^2 + 1 – 16x^6 – 8x^3 – 1 = 36
-> (16x^6-16x^6) + (8x^3-8x^3) + (1-1) – 9x^2 = 36
-> -9x^2 = 36
-> x^2 = -4
-> x ∈ ∅
Vậy x ∈ ∅

Trả lời